Salp swarm algorithm for optimal load balancing in low voltage networks - Ibrahim Altawil; Ehab Obeidat; Khaled A. Mahafzah; Zaid Albataineh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Distribution networks for low voltage (LV) are three-phase networks. It mostly serves single-phase end customers with a variety of load characteristics. Because each customer's load behavior differs, the current on the LV networks feeder is shared unequally, leading in an im-balance problem. This research investigates an efficient distribution of single-phase loads amongst three phase networks using the salp swarm algorithm (SSA) to phase swap consumers between phases. Customers are rearranged and their loads are switched from heavy to light to achieve phase shifting. Jordan's electricity distribution company (EDCO) has provided a full load feeder as a case study. The results of switching loads to a three-phase feeder show that the im-balance index and power losses can be decreased significantly.